KONTRIBUSI KEKUATAN OTOT LENGAN, OTOT TUNGKAI DAN KOORDINASI MATA TANGAN TERHADAP KEMAMPUAN SMASH BOLA VOLI PADA TIM BARENGKO SALUTUBU - Arjun, Aditio; Nur, Suaib; Anuar, Arman Bin; Agus Ismail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the contribution of arm muscle strength, leg muscle strength, and hand-eye coordination to the smash ability in volleyball players of the Barengko Salutubu Team. The research employed a quantitative approach using a correlational method. The population consisted of all 15 male volleyball players of the Barengko Salutubu Team, who were also selected as the sample using a total sampling technique. The instruments used included physical tests to measure arm muscle strength (push-up), leg muscle strength (standing broad jump), hand-eye coordination (ball throw and catch), and smash ability. Descriptive analysis results indicated that the players’ average physical abilities and smash performance were in the good category. Pearson correlation tests showed that all three independent variables had a significant relationship with smash ability: arm muscle strength (r = 0.868; p < 0.001), leg muscle strength (r = 0.651; p = 0.009), and hand-eye coordination (r = 0.744; p = 0.001). Multiple linear regression analysis revealed that all variables contributed significantly, with arm muscle strength being the dominant factor. The coefficient of determination (R²) of 0.899 indicates that 89.9% of the variability in smash ability can be explained by the three variables. Therefore, it can be concluded that arm muscle strength, leg muscle strength, and hand-eye coordination all contribute significantly, both individually and collectively, to volleyball smash ability. The study recommends that coaches focus on developing these physical components in athletes’ training programs.